NPInter v5.0: ncRNA interaction database in a new era. Issue Volume 51:Issue D1(2023) (14th November 2022) - Zheng, Yu; Luo, Huaxia; Teng, Xueyi; Hao, Xinpei; Yan, Xiaoyu; Tang, Yiheng; Zhang, Wanyu; Wang, Yuanxin; Zhang, Peng; Li, Yanyan; Zhao, Yi; Chen, Runsheng; et al.
Abstract: Noncoding RNAs (ncRNAs) play key regulatory roles in biological processes by interacting with other biomolecules. With the development of high-throughput sequencing and experimental technologies, extensive ncRNA interactions have been accumulated. Therefore, we updated the NPInter database to a fifth version to document these interactions. ncRNA interaction entries were doubled from 1 100 618 to 2 596 695 by manual literature mining and high-throughput data processing. We integrated global RNA–DNA interactions from iMARGI, ChAR-seq and GRID-seq, greatly expanding the number of RNA–DNA interactions (from 888 915 to 8 329 382). In addition, we collected different types of RNA interaction between SARS-CoV-2 virus and its host from recently published studies. Long noncoding RNA (lncRNA) expression specificity in different cell types from tumor single cell RNA-seq (scRNA-seq) data were also integrated to provide a cell-type level view of interactions. A new module named RBP was built to display the interactions of RNA-binding proteins with annotations of localization, binding domains and functions. In conclusion, NPInter v5.0 (http://bigdata.ibp.ac.cn/npinter5/ ) provides informative and valuable ncRNA interactions for biological researchers.